(Canangium odoratum Baill)(Study on The Effect of Zeolite Used and Temperature of Bleaching In Improving the quality of Cananga oil (canangium odoratum Baill) - Sudibyo, Agus; Astuti, Juli (Balai Besar Industri Agro, 2005)
The aim of this study was to improve the quality of cananga oil from Bolyolali Central of Java by bleached treatment with zeolite and tartaric acid.were heated at 50 and 60 celsius degree in boiled water bath with active zeolite (A1)and natural zeolite (A2) at 3%(B1),6% (B2)and 9%(B3) and also with a tartaric acid at 3 percent using magnetic stirrer at 250 rpm for 60 minutes.The control was cananga oil without treatment.After filtered the cananga oil were analyzed for the yield, colour tranmission,metal content, ester number,specific gravity at 20 celsius degree,rotary index,optic rotation and solution in 95% of ethnol.The results indicated that the best treatment in term of he yield,tranmission,ester number and metal content was that treating cananga oil with 6% of active zeolite and 3% of tartaric acid at 50 celsius degree.Active zeolite was more affective than natural zeolite in absorbing the undesirable containment.